68Ga-PSMA Expression in Pseudoangiomatous Stromal Hyperplasia of the Breast. (January 2017) - Malik, Dharmender; Basher, Rajender K.; Mittal, Bhagwant Rai; Jain, Tarun Kumar; Bal, Amanjit; Singh, Shrawan Kumar
Abstract : Abstract: 68 Ga-labeled prostate-specific membrane antigen ligand PET-CT has emerged as a promising technique to evaluate the extent of disease in patients with prostate carcinoma. We are reporting a 63-year-old man with prostatic carcinoma subjected to 68 Ga–prostate-specific membrane antigen ligand PET-CT for initial staging. In addition to the radiotracer uptake in known primary site (prostate), focal increased radiotracer uptake was also noticed in the left breast. Subsequent biopsy of the breast lesion revealed PASH (pseudoangiomatous stromal hyperplasia), which is a benign mesenchymal proliferative lesion that may present clinically as palpable mass requiring further evaluation to rule out malignancy.